Development of Auto Roll Prayer Mat for Musolla - Sagitarius, Muhammad Dafit Herman; Morsin, Marlia; Mahmud, Farhanahani; Md Shah, Nur Zehan An’Nisa; Razali, Nur Liyana (Journal of Electronic Voltage and Application, 2020)
During Friday or ‘Hari Raya’ festival, mosques will be flooded with Muslims who wish to perform prayers. Normally, mosques or ‘musolla’ require a large prayer space and certainly committees of the mosques would like to provide a comfortable space to perform prayer. However, the problem comes when the area provided is small and therefore the mosque’s person in charge which is known as ‘tok siak’ needs to prepare additional prayer mat for them. In this study, Auto Roll Prayer Mat (ARPM) is a new innovation idea system that was designed to ease the burden and at the same time to make the task more efficient. ARPM can perform in two conditions, which are it can stretched out prayer mat automatically and the other is that the prayer mat also can roll back to its actual condition. The overall system was supported with a main component of the system which was a power window motor accompanied with pulse width modulation (PWM) motor controller circuit. Moreover, ARPM was also equipped with secondary function of an automatic cleaning process where the ARPM system was able to clean the prayer mat by using a servo motor and Arduino UNO microcontroller, while simultaneously stretching out the prayer mat.